Basic chemistry - Timberlake, Karen C.; Timberlake, William (Pearson Education Limited, 2017)
Basic Chemistry introduces students to the essential scientific and mathematical concepts of general chemistry. With accessible language and a moderate pace, the text is easy-to-follow for first-time chemistry students, as well as those hoping to renew their studies of the subject.